Growth performance of Tectona grandis provenance trial in Tanzania - Opiyo, Anthony P.; Chamshama, Shabani A.O.; Mwambusi, Japhet N.; Mushumbusi, Revocatus P. (Agriculture and Natural Resources, 2023)
Importance of the work: Teak (Tectona grandis L.f.) is of significant economic importance. It was introduced to Tanzania in the early 20th century for commercial purposes. However, there is limited available information regarding the growth performance of teak seeds obtained from various localities. Objectives: To assess the performance of teak provenances at Longuza Forest Plantation, Tanzania. Materials & Methods: The study employed a randomized complete block design with eight replications, each consisting of six trees, to evaluate 12 provenances of 11-year-old teak trees from 41 families. These trees were planted in the same area with similar climatic conditions. The assessment parameters included survival, diameter at breast height (1.3 m above the base) over bark (Dbh), total tree height (Ht), basal area at breast height (BA), total tree above ground volume (Vol) and the mean annual increment (MAI). The statistical analysis was performed using SAS® software version 9.4 and its Rank procedures. Results: There were no significant (p > 0.05) differences in survival among the tested provenances. However, highly significant (p<0.0001) differences were observed for Dbh, Ht, Vol, BA and MAI among the provenances and families, with mean (± SD) values of survival, Dbh, Ht, Vol, BA and MAI of 68.70 ± 5.64%, 21.35 ± 4.04 cm, 18.65 ± 2.2 m, 304.83 ± 135.37 m³/ha, 9.96 ± 3.60 m²/ha and 27.71 ± 12.30 m³/ha/yr, respectively. The findings revealed the superior performance of the East Africa Longuza seed, East Africa Longuza provenance trial and East Africa Longuza progeny trial provenances. Main finding: There were significant variations in all tested parameters except survival. The Tanzanian provenances showed superior performance in both growth and productivity. Thus, it was recommended to plant these provenances on a large scale in Longuza and other areas with similar climatic and soil conditions